Pengaruh Model Kooperatif Tipe Index Card Match Berbantuan Media Wordwall Terhadap Kemampuan Membaca Pemahaman Siswa SD - Rika Putri Pertiwi; Nadia Tiara Antik Sari; Nenden Permas Hikmatunisa (JURNAL ASIMILASI PENDIDIKAN, 2026)
The main problem underlying this study is the low reading comprehension skills of Grade V elementary school students. This study aims to examine the effect of the Index Card Match (ICM) cooperative learning model assisted by Wordwall media on students' reading comprehension skills, and to compare its improvement with the Student Teams Achievement Divisions (STAD) model assisted by PowerPoint. A quasi-experimental method with a nonequivalent control group design was employed. The sample consisted of 55 students (28 in the experimental class and 27 in the control class), selected through cluster random sampling. Data processing was conducted on test data in the form of pre-test and post-test, supported by non-test data in the form of observation sheets. The results showed a positive and significant effect of 69.3% from the implementation of the ICM cooperative learning model assisted by Wordwall media on students' reading comprehension skills. Furthermore, a significant difference in improvement was found between the two classes (Sig. = 0.000 < 0.05), with the experimental class achieving an N-Gain of 0.56 (moderately effective) and the control class 0.33 (ineffective). Therefore, the Index Card Match cooperative learning model assisted by Wordwall media is proven to be more effective in improving reading comprehension skills of Grade V elementary school students compared to the STAD model assisted by PowerPoint.